PENGARUH WORD OF MOUTH, KUALITAS PELAYANAN, DAN LOKASI TERHADAP KEPUTUSAN MENJADI PELANGGAN PADA BMT BABUSSALAM MOJOAGUNG JOMBANG - Nur Ainul Mutmainnah; Nihayatu Aslamatis Solekah (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This research is a type of quantitative research. The population in this study were all customers who had savings accounts at BMT Babuussalam Mojoagung Jombang. The sampling technique uses accidential sampling method. The sample in this study amounted to 100 people who were calculated using the Rao formula. Using multiple linear regression tests with the aim of knowing the effect of variable x, namely word of mouth, service quality and location on the decision to be a customer. Based on the tests that have been carried out, this study has the result that partially word of mouth has no effect on the decision to be a customer at BMT Babussalam Mojoagung Jombang. This study also has the result that service quality and location partially have an effect on the decision to be a customer at BMT Babussalam Mojoagung Jombang. In addition to partial influence, there is also a simultaneous effect, namely together the word of mouth variables, service quality and location affect the decision to be a customer at BMT Babussalam Mojoagung Jombang. Keywords: Word of Mouth, Service Quality, Location, Purchase Decision